2017
DOI: 10.1088/1741-4326/aa86fe
|View full text |Cite|
|
Sign up to set email alerts
|

Multiscale interaction between a large scale magnetic island and small scale turbulence

Abstract: Multiscale interaction between the magnetic island and turbulence has been demonstrated through simultaneous two-dimensional measurements of turbulence and temperature and flow profiles. The magnetic island and turbulence mutually interact via the coupling between the electron temperature (T e ) gradient, the T e turbulence, and the poloidal flow. The T e gradient altered by the magnetic island is peaked outside and flattened inside the island. The T e turbulence can appear in the increased T e gradient region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 57 publications
11
73
0
Order By: Relevance
“…It has been experimentally and numerically pointed out that the large magnetic island can generate strong shear flow around it, which substantially suppress the local turbulence and play an important role in the formation of the internal transport barrier (ITB). 6,15,32 Indeed, in our simulation, we observe that the vortex mode (d/ 1,2 ) can generate clear helical shear flow around the magnetic island. We define the helical flow as n ¼ mh À nf;…”
Section: Effects Of the Magnetic Island On Itg Turbulencementioning
confidence: 50%
See 2 more Smart Citations
“…It has been experimentally and numerically pointed out that the large magnetic island can generate strong shear flow around it, which substantially suppress the local turbulence and play an important role in the formation of the internal transport barrier (ITB). 6,15,32 Indeed, in our simulation, we observe that the vortex mode (d/ 1,2 ) can generate clear helical shear flow around the magnetic island. We define the helical flow as n ¼ mh À nf;…”
Section: Effects Of the Magnetic Island On Itg Turbulencementioning
confidence: 50%
“…4 for the island case. The turbulence intensity can be represented by the ion density varianceñ 2 i ðrÞ calculated as…”
Section: Effects Of the Magnetic Island On Itg Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…In practice we use a short-time Fourier transformation (STFT) which averages the Fourier coefficients obtained from FFTs calculated on slightly shifted time windows. Spectral quantities calculated off local T e fluctuations, such as the cross coherence or the cross phases, are used to identify macro-scale structures, so called magnetic islands, as well as micro-scale instabilities in the plasma [Cho17]. Understanding the physics resulting in magnetic islands is important for plasma confinement, and avoiding sudden loss of plasma control, known as a disruption.…”
Section: Electron Cyclotron Emission Imagingmentioning
confidence: 99%
“…The coupling between the transport bifurcation and the MHD bifurcation found as a bifurcation of the magnetic island state [19] is also discussed in section 4. The interplay between MHD instability and turbulent transport is recognized to be an important topic in toroidal plasmas [20,21]. In this review article, the various bifurcation phenomena observed in the toroidal magnetically confined plasma are reviewed and the physics mechanism for the bifurcation phenomena is discussed.…”
Section: Introductionmentioning
confidence: 99%